Regenerative Capacity of Macrophages for Remyelination - Rawji, Khalil S.; Mishra, Manoj K.; Yong, V. Wee (Frontiers in Cell and Developmental Biology, 2016)
White matter injury, consisting of loss of axons, myelin and oligodendrocytes, is common in many neurological disorders and is believed to underlie several motor and sensory deficits. Remyelination is the process in which the insulative myelin sheath is restored to axons, thereby facilitating recovery from functional loss. Remyelination proceeds with oligodendrocyte precursor cells that differentiate into oligodendrocytes to synthesize the new myelin sheath after demyelination. This process is influenced by several factors, including trophic factors, inhibitory molecules in the lesion microenvironment, age of the subject, as well as the inflammatory response. Currently studied strategies that enhance remyelination consist of pharmacological approaches that directly induce oligodendrocyte precursor cell differentiation or using agents to neutralize the inhibitory microenvironment. Another strategy is to harness a reparative inflammatory response. This response, coordinated by central nervous system resident microglia and peripherally-derived infiltrating macrophages, has been shown to be important in the remyelination process. These innate immune cells perform important functions in remyelination, including the proteolysis and phagocytosis of inhibitory molecules present in the lesion microenvironment, the provision of trophic and metabolic factors to oligodendrocyte precursor cells, in addition to iron handling capacity. Additionally, an initial pro-inflammatory phase followed by a regulatory/anti-inflammatory phase has been shown to be important for oligodendrocyte precursor cell proliferation and differentiation, respectively. This review will discuss the beneficial roles of macrophages/microglia in remyelination and discuss therapeutic strategies to obtain the optimal regenerative macrophage phenotype for enhanced remyelination.